Reappraising Abstract Paintings after Exposure to Background Information - Park, Seongmin A.; Yun, Kyongsik; Jeong, Jaeseung (PLOS ONE, 2015)
Can knowledge help viewers when they appreciate an artwork? Experts’ judgments of the aesthetic value of a painting often differ from the estimates of naïve viewers, and this phenomenon is especially pronounced in the aesthetic judgment of abstract paintings. We compared the changes in aesthetic judgments of naïve viewers while they were progressively exposed to five pieces of background information. The participants were asked to report their aesthetic judgments of a given painting after each piece of information was presented. We found that commentaries by the artist and a critic significantly increased the subjective aesthetic ratings. Does knowledge enable experts to attend to the visual features in a painting and to link it to the evaluative conventions, thus potentially causing different aesthetic judgments? To investigate whether a specific pattern of attention is essential for the knowledge-based appreciation, we tracked the eye movements of subjects while viewing a painting with a commentary by the artist and with a commentary by a critic. We observed that critics’ commentaries directed the viewers’ attention to the visual components that were highly relevant to the presented commentary. However, attention to specific features of a painting was not necessary for increasing the subjective aesthetic judgment when the artists’ commentary was presented. Our results suggest that at least two different cognitive mechanisms may be involved in knowledge- guided aesthetic judgments while viewers reappraise a painting.